Reliability estimation of corroded RC structures based on spatial variability using experimental evidence, probabilistic analysis and finite element method. (1st August 2019) - Zhang, Mingyang; Song, Huijuan; Lim, Sopokhem; Akiyama, Mitsuyoshi; Frangopol, Dan M.
Highlights: Effects of current density, rebar size, and fly ash on steel corrosion are studied. Effects of spatial steel corrosion on structural behavior of RC beams are examined. Reliability of corroded RC beams is assessed using FE and probabilistic methods. Spatial steel corrosion was modeled in FE method using Gumbel distribution. Element length and correlation of steel weight loss are considered. Abstract: Corrosion of steel reinforcement is spatially distributed over RC structures due to several factors such as different environmental exposure, concrete cover, and concrete quality, among others. Ignoring the effect of spatial variability is a drastic simplification for the prediction of the remaining service life of RC structures. Therefore, it is essential to identify the factors influencing the spatial steel corrosion and structural performance of corroded RC structures. In this paper, an experimental research is conducted to study the effects of main parameters (i.e. current density, concrete cover, rebar diameter, and fly ash) on the spatial variability associated with steel weight loss, corrosion crack, and structural behavior of accelerated-corrosion RC beams using X-ray radiography and digital image processing. The test results showed that low current density ( Icorr  ≤ 50 µA/cm 2 ) induced highly non-uniform corrosion associated with few large pits and cracks at certain locations while higher current density produced more uniform corrosion and cracks over the beam length. Gumbel distribution parameters were derived from the steel weight loss data for modeling spatial steel corrosion. A novel approach was established to assess the reliability of RC structures using finite element (FE) analysis and probabilistic analysis considering the effects of modeled spatial variability of steel weight loss based on X-ray photographs. Using the Gumbel distribution parameters derived from the steel weight loss data associated with higher current density may underestimate the non-uniformity of corrosion distribution which can lead to an overestimation of the load capacity of corroded RC structures.